2019
DOI: 10.20402/ajbc.2019.0314
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Usability of Cyclodextrin as a Cosmetic Ingredient

Abstract: Skin is the outermost barrier of the body, making it vulnerable to various external stimuli that can directly influence skin aging. To maximize the impact of cosmetics that delay skin aging, the stabilization of cosmetic ingredients is necessary. In addition to microencapsulation, liposome, and liquid crystal methods to increase the bioavailability of cyclodextrin, various studies have been conducted that utilize its structural characteristics to improve its properties of solubility, stability, and sustained r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Their ability to encapsulate guest molecules makes CDs superb agents for commercial cosmetic applications. This trait endows a plethora of advantages to the CD-encapsulated cosmetic product, including improved physical and chemical stability against light and oxidation, more controlled release of volatile compounds and fragrances, increased solubilization of insoluble components, easier removal of unpleasant odors or undesired external smells, a straightforward modification process for the formulation from liquids or oil powder, improved skin penetration capabilities, and slowed release of the active ingredients via the application of nanotechnology or nanosystems [ 70 , 71 , 72 , 73 , 74 ]. Recently, Mori et al reported that the complexation of HP-γ-CD/trans-ferulic acid (t-FA) improved the anti-UV properties of eco-friendly sunscreens and increased the solubility of t-FA, an all-natural UV-absorbing ingredient derived from rice bran [ 75 ].…”
Section: Applications Of CD Inclusion Complexes In the Solid/solutmentioning
confidence: 99%
“…Their ability to encapsulate guest molecules makes CDs superb agents for commercial cosmetic applications. This trait endows a plethora of advantages to the CD-encapsulated cosmetic product, including improved physical and chemical stability against light and oxidation, more controlled release of volatile compounds and fragrances, increased solubilization of insoluble components, easier removal of unpleasant odors or undesired external smells, a straightforward modification process for the formulation from liquids or oil powder, improved skin penetration capabilities, and slowed release of the active ingredients via the application of nanotechnology or nanosystems [ 70 , 71 , 72 , 73 , 74 ]. Recently, Mori et al reported that the complexation of HP-γ-CD/trans-ferulic acid (t-FA) improved the anti-UV properties of eco-friendly sunscreens and increased the solubility of t-FA, an all-natural UV-absorbing ingredient derived from rice bran [ 75 ].…”
Section: Applications Of CD Inclusion Complexes In the Solid/solutmentioning
confidence: 99%
“…나노 입자로 만드는 과정과 제형의 안정화 공정을 감안 하여 다층유화기술을 제형에 적용하였기에 가능한 결과이다 . 또한 CD 포접 복합체는 외부적인 요인으로부터 보호받을 수 있을 뿐만 아니라 산소, 열 빛에 대한 안정성이 강화되고 수용해 도를 증가 시킬 수 있음을 시사한다 (Lee et al, 2019). , 27: 427-435, 2019…”
Section: ) 안티에이징 화장품의 안정성 평가unclassified